Health and Sickness in Henry of Herford’s Catena aurea entium - Palazzo, Alessandro (E-theca OnLineOpenAccess Edizioni, 2026)
Henry of Herford frequently addresses medical topics throughout his encyclopedia, the Catena aurea entium. The paper offers an overview of the sections that deal with health, sickness, and diseases. While including key texts of medieval medical literature, Henry’s ‘medical library’ has a specific focus on practical medicine, pharmacology, and the regimen. The paper also includes editions of some questions dedicated to specific diseases.